Comparison among four cursors arthropod groups biomass in three different vegetational composition sites of the landscape (Igrapiúna, Bahia, Brazil) - Xavier, Ariane Lima; Galindo, Toni Pablo Souto; Ferreira, Patrícia Alves; Moura, Perimar Espírito Santo de; Almeida, Carolina Estevam de Pinho (SITIENTIBUS série Ciências Biológicas, 2008)
Areas with forested matrix and agricultural systems can minimize the effects of fragmentation by connecting the remaining native vegetation. This study evaluated the biomass of four groups of cursors arthropods that occur in the rubber-tree matrix and in the forested fragments in early and advanced regeneration stage, aiming to verify the permeability of this monoculture (Havea brasiliensis) and the possibility of using it to connect isolated fragmented areas. There were eight randomized points in the three different vegetable composition and four pitfalls were used for each point. The sampled arthropods were separated by groups (Order) and their biomasses (humid weight) were measured. The chosen Orders were Araneae, Dermaptera, Blattaria and Isopoda. According to the most abundant groups, Araneae and Isopoda were chosen to the rubber-tree plantation as Dermaptera and Blattaria were to the forest areas. The biomass scores showed bigger amplitude variation among primary forest sites and fragments than in the rubber-tree plantation. There was no significant difference among the three areas. However the analyses of the interactions among the factor levels (three different vegetable composition compared two to two) has pointed out significance between the forested fragments in regeneration advanced stage and the rubber-trees plantation. The inferior values of biomass of the plantation of the rubber-trees can indicate its inefficiency to connect remaining native vegetation.